If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + 6m = 5m Solving 8 + 6m = 5m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-5m' to each side of the equation. 8 + 6m + -5m = 5m + -5m Combine like terms: 6m + -5m = 1m 8 + 1m = 5m + -5m Combine like terms: 5m + -5m = 0 8 + 1m = 0 Add '-8' to each side of the equation. 8 + -8 + 1m = 0 + -8 Combine like terms: 8 + -8 = 0 0 + 1m = 0 + -8 1m = 0 + -8 Combine like terms: 0 + -8 = -8 1m = -8 Divide each side by '1'. m = -8 Simplifying m = -8
| 752=4(x+19) | | FV=1000(1+0.02)12 | | 12-12+7= | | 24x=180n-360 | | 8+6m=5 | | y=-2x^2+6 | | x^2-6x+9x=0 | | 3+6-16= | | 2-5x=x+14 | | 8w=9+5w | | 7n+2(2n-4)-2= | | 3y+2(2y-3)=8-7(y-2) | | 7x-10=11x+6 | | 3c=-8+5c | | -12=3x-7 | | 0.45x+0.33=0.66 | | (8y-17)=(6y+5) | | (a*5)*6a= | | 9+1x=3+7 | | -6+4T=3t | | 12-(4m+7)=3+2m-16 | | -0.2(6.5n-2)=0.848 | | -3=x/12 | | (12y-y)=11 | | 4(5-2y)=2(1-y) | | 0=-3x^3-3x^2+168x | | -3-7x=-66 | | -3-7=-66 | | y=7-7x | | -12=2x-7 | | -2x-25=-5x-7 | | 50*x=109 |